Duas décadas de cooperação internacional ambiental: análise da cooperação entre Brasil e Alemanha no período dos governos de Gerhard Schröder e Angela Merkel (1998-2018). - Knebel , Léo Casagrande (Universidade do Vale do Rio dos Sinos, 2021)
This work is a descriptive study, which seeks to understand the bilateral relations between Brazil and Germany, within the scope of international environmental cooperation. The purpose of the study is to answer how the bilateral environmental cooperation between these countries lasts, specially because they have different positions about the subject. Through the analysis of a predetermined period between the administrations of Gerhard Schröder (1998-2005) and Angela Merkel (2005-2018), using the qualitative methodology, a description of the foreign and environmental policies of Brazil and Germany and the phenomenon of their environmental cooperation is provided. It also presents the motivations, benefits, and challenges of environmental cooperation as well as the description of their international cooperation projects for development. As theoretical framework, the present study focuses on the phenomenon of complex interdependence, by Keohane and Nye (2001), and the understanding of how the international regime, verified by Krasner (2012), helps the mechanisms of international cooperation. In the end, it is understood that international environmental cooperation between Brazil and Germany continues to take place, even with the presence of variations in external and environmental policies of these governments.
Keywords: Cooperação Internacional Ambiental; Interdependência Complexa; Regimes Internacionais; Brasil; Alemanha; International Environmental Cooperation; Complex Interdependence; International Regimes; Brazil; German